Induction Cookers Use a Hybrid System Powered by Recycled Batteries - RAHMADHANI BANUREA; Fathurrahman Fathurrahman; Abdul Floranda (Talenta Publisher, 2025)
Traditional stoves cause fires due to problems and accidents. Induction stoves mitigate this concern by reducing the likelihood of flames and the risk of fire. Induction cookers do not produce flames. The power supply, combined with a recycled 12V 16850 Lithium-Ion battery and a bridge diode, constitutes the primary voltage source that provides 200W of power to activate the ZVS module. Then, connect the ACS712 sensor as a current sensor. The ATMega328 microcontroller controls the system, which is programmed to read and respond to sensor inputs. The sensor results are displayed on the I2C LCD as soon as the ZVS module is powered, when a load is placed on the coil. The results obtained from the first to third minutes of the study showed a water temperature ranging from 32.6°C to 64.9°C with a stable current of 17.5 A. From the fourth to the eighteenth minute, the current decreased drastically to 8A, resulting in an excessively long water heating duration of up to eighteen minutes to reach a temperature of 100°C. This occurs because the ZVS module's working system is not functioning correctly. For further research, consider using a power supply and a higher-voltage lithium-ion battery to accelerate the heating process.